Does green intellectual capital matter for reverse logistics competency? The role of regulatory measures - Saglam, Yesim Can (Emerald Group Publishing Ltd, 2023)
PurposeDespite its potential advantages in a wide range of environmental subjects, green intellectual capital has received scant attention in the field of reverse logistics (RL). This research focuses on exploring the relationship between significant green intellectual capital assets (namely green human capital, green relational capital, and green structural capital) and RL competency. The moderating role of regulatory measures was also hypothesized and tested.Design/methodology/approachA survey-based research instrument was employed to collect data and partial least square structural equation modeling (PLS-SEM) based approach was utilized to test hypotheses.FindingsThe results indicate that green relational capital and green structural capital are positively associated with RL competency. Interestingly, regulatory measures are also found only to moderate the relationship between green human capital and RL competency.Originality/valueThis study extends the present literature by enhancing the knowledge of RL competency, which is a critical ingredient of the circular economy, by revealing the relation with green intellectual capital. Additionally, this study offers insights into the manufacturing industry, especially in emerging economies for academics and practitioners.
Keywords: Green intellectual capital; Reverse logistics; Sustainability; Supply chain management; Regulatory measures